The indirect response of an aquatic ecosystem to long‐term climate‐driven terrestrial vegetation in a subalpine temperate lake. (15th December 2017) - Beck, Kristen K.; Fletcher, Michael‐Shawn; Kattel, Giri; Barry, Linda A.; Gadd, Patricia S.; Heijnis, Henk; Jacobsen, Geraldine E.; Saunders, Krystyna M.
Abstract: Aim: To assess whether climate directly influences aquatic ecosystem dynamics in the temperate landscape of Tasmania or whether the effects of long‐term climatic change are mediated through the terrestrial environment (indirect climate influence). Location: Paddy's Lake is located at 1065 m a.s.l. in temperate north‐west Tasmania, a continental island south‐east of mainland Australia (41°15–43°25′ S; 145°00–148°15′ E). Methods: We developed a new 13, 400 year (13.4 kyr) palaeoecological dataset of lake sediment subfossil cladocerans (aquatic grazers), bulk organic sediment carbon (C%) and nitrogen (N%) and δ 13 C and δ 15 N stable isotopes. Comparison of this new data was made with a recently published pollen, geochemistry and charcoal records from Paddy's Lake. Results: Low cladoceran diversity at Paddy's Lake is consistent with other temperate Southern Hemisphere lakes. The bulk sediment δ 15 N values demonstrate a significant lagged negative response to pollen accumulation rate (pollen AR). Compositional shifts of dominant cladoceran taxa ( Bosmina meridionalis and Alona guttata ) occur following changes in both pollen AR and pollen (vegetation) composition throughout the 13.4 kyr record at Paddy's Lake. The δ 15 N values demonstrate a significant positive lagged relationship to the oligotrophic:eutrophic cladoceran ratio. Main conclusions: Long‐term changes in cladoceran composition lag changes in both pollen AR and terrestrial vegetation composition. We interpret pollen AR as reflecting climate‐driven changes in terrestrial vegetation productivity and conclude that climate‐driven shifts in vegetation are the principal driver of the cladoceran community during the last ca. 13.4 kyr. The significant negative lagged relationship between pollen AR and δ 15 N reflects the primary control of vegetation productivity over within‐lake nutrient status. Thus, we conclude that the effects of long‐term climate change on aquatic ecosystem dynamics at our site are indirect and mediated by the terrestrial environment. Vegetation productivity controls organic soil development and has a direct influence over lake trophic status via changes in the delivery of terrestrial organic matter into the lake.